American constitutional law - Tribe, Laurence H. (New York, N.Y. : Foundation Press, 2003)
This treatise on constitutional law is organized around issues, or constitutional functions, rather than being a sequential discussion of the text to the Constitution. Professor Tribe provides analysis of constitutional law doctrine and policy. The text is heavily footnoted with references to treatises, law review articles, the U.S. Code, and Supreme Court cases. Volume I concentrates on the Constitution's provisions for government structure and on how constitutional structure helps guarantee protection of substantive rights and liberties.
Approaches to Constitutional Analysis -- Model I-The Model of Separated and Divided Powers -- Federal Judicial Power -- Federal Executive Power -- Federal Legislative Power: Congressional Authority and the Implications of State Sovereignty -- Union-Preserving Aspects of Federalism: Limits on State and Local (and Occasionally Federal) Power -- Models Beyond the Seperation and Division of Powers: The Civil War as a Watershed in the Direct Federal Protection of Individual Rights -- Model II-The Model of Implied Limits on Government: The Rise and Fall of Contractual Freedom and of Substantive Due Process in the ''Natural Law'' Style -- Appendix-The Justices of the Supreme Court.
Includes bibliographical references and index.
Keywords: Constitutional law -- United States